2020
DOI: 10.3390/f11050528
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Root Traits under Competition for a Nutrient-Rich Patch Depends on Tree Species and Possesses a Large Congruency between Intra- and Interspecific Situations

Abstract: Belowground competition is an important structuring force in terrestrial plant communities. Uncertainties remain about the plasticity of functional root traits under competition, especially comparing interspecific vs. intraspecific situations. This study addresses the plasticity of fine root traits of competing Acer pseudoplatanus L. and Fagus sylvatica L. seedlings in nutrient-rich soil patches. Seedlings’ roots were grown in a competition chamber experiment in which root growth (biomass), morphological and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Trait plasticity may “enhance species’ ability to coexist” (Pfennig et al 2006), but this depends on other factors (see review by Turcotte and Levine 2016). Because plasticity has the potential to reduce niche overlap, we might expect competitors to exhibit plasticity in response to severe conditions, such as drought (Lak et al 2020, Lorts and Lasky 2020). We found plasticity in all traits for Potentilla in intraspecific or interspecific competition, and for root mass and root : shoot ratios for Leucanthemum in intraspecific competition.…”
Section: Discussionmentioning
confidence: 99%
“…Trait plasticity may “enhance species’ ability to coexist” (Pfennig et al 2006), but this depends on other factors (see review by Turcotte and Levine 2016). Because plasticity has the potential to reduce niche overlap, we might expect competitors to exhibit plasticity in response to severe conditions, such as drought (Lak et al 2020, Lorts and Lasky 2020). We found plasticity in all traits for Potentilla in intraspecific or interspecific competition, and for root mass and root : shoot ratios for Leucanthemum in intraspecific competition.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed root phenotypic plasticity for all features having CoV values ≥ 30% and for which there was a significant difference between genotypes. We adapted the procedure of Lak et al [ 42 ] to calculate RDPI. The RDPI ranges from 0 (no plasticity) to 1 (maximum plasticity) [ 20 , 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…This finding suggests that interactions between roots of different species growing together did not affect root litter quality. This is in contrast with the limited evidence showing that intraspecific and interspecific interactions can induce changes in plant litter quality (Genung et al, 2013;Lak et al, 2020;Semchenko et al, 2017). For instance, it has been shown that root N concentrations under interspecific competition were lower than under intraspecific competition and single plants (Lak et al, 2020).…”
Section: Slower Decomposition Of Mixed-species Than Single-species Li...mentioning
confidence: 69%
“…This is in contrast with the limited evidence showing that intraspecific and interspecific interactions can induce changes in plant litter quality (Genung et al, 2013;Lak et al, 2020;Semchenko et al, 2017). For instance, it has been shown that root N concentrations under interspecific competition were lower than under intraspecific competition and single plants (Lak et al, 2020). Also, more genetically diverse mixtures of the same species produced root litter with higher N content (Semchenko et al, 2017).…”
Section: Slower Decomposition Of Mixed-species Than Single-species Li...mentioning
confidence: 81%